Key Performance Indicators (KPI) of Information Systems Project Management (International Journal of Financial, Administrative and Economic Sciences, 2023)
Performance measurements are used in project management and quality processes to determine and communicate status and accomplishments measured against specific objectives, schedules, and milestones. This paper is concerned with the calculation of performance indicators of Information Systems Project Management (ISPM). It clarifies the relationships between ISPM domains, performance metrics, and performance indicators. This paper presents a proposed list of metrics for ISPM. Based on these ISPM metrics and a combination of statistical techniques, we built a model for calculating ISPM performance indicators. The quality reviewers can use this model to evaluate and track the performance of IS project managers.
Keywords: Key Performance Indicators; Projects Management; Software Projects; Metrics; Measures